Effects of momordica charantia aqueous extract on cutaneous wond healing in diabetic rats - Normaliza O; Norhazilah M; Noor Fadzilah Z; Mohamad Fairuz Y; Azian AL (UKM Press, 2024)
Diabetes mellitus is a chronic disorder that affects an increasing number of people worldwide. Impaired wound healing is one of the complications that can lead to infection, gangrene and amputation. Besides current standard medication, some traditional herbs have been used to treat this disease. Momordica charantia or bitter gourd is known to possess antioxidant, antibacterial and antihyperglycaemic properties. It has also been used for wound healing.